Simplicidad y claridad estructurales: la producción de cláusulas relativas en castellano - Cerrón-Palomino López, Alvaro (2011)
This article constitutes a psycholinguistic approach to the study of the occurrence of relative pronouns (RP) in relative clauses (RC) in Spanish, considering that this type of construction is common in nonstandard varieties of the language and are often censored in the descriptive grammars.Since there are no experimental studies on the subject in Spanish, this work is based partly on a study conducted by Ferreira and Swets (2004) on a similar phenomenon in English. The research aims to determine whether direct object and oblique RP are a repair strategy for insufficiently planned sentences and if the subject RP may appear in controlled situations derived from the contrast of two possible antecedents